Vitamin D deficiency contributes to the diabetic kidney disease progression via increase ZEB1/ZEB2 expressions - Cláudia Silva Souza; Amanda Lima Deluque; Beatriz Magalhães Oliveira; Ana Lívia Dias Maciel; Cleonice Giovanini; Patrícia Aline Boer; Francisco José Albuquerque de Paula; Roberto Silva Costa; Heloísa Della Colleta Franscecato; Lucas Ferreira de Almeida; Terezila Machado Coimbra (Nutrition & Diabetes, 2023)
Abstract Background Diabetic kidney disease (DKD) remains one of the main causes of end-stage renal disease (ESRD) and mortality in diabetic patients worldwide. Vitamin D deficiency (VitDD) is one of the main consequences of different chronic kidney disease (CKD) types and is associated with rapid progression to ESRD. Nevertheless, the mechanisms that lead to this process are poorly understood. This study aimed to characterize a model of diabetic nephropathy progression in VitDD and the epithelial-mesenchymal-transition (EMT) role in these processes. Methods Wistar Hannover rats received a diet with or without VitD before type 1 diabetes (T1D) induction. After this procedure, the rats were accompanied for 12 and 24 weeks after T1D induction and the renal function, structure, cell transdifferentiating markers and zinc finger e-box binding homeobox 1/2 (ZEB1/ZEB2) contribution to kidney damage were evaluated during the DKD progression. Results The results showed an increase in glomerular tuft, mesangial and interstitial relative areas and renal function impairment in VitD-deficient diabetic rats compared to diabetic rats that received a VitD-containing diet. These alterations can be associated with increased expression of EMT markers, ZEB1 gene expression, ZEB2 protein expression and TGF-β1 urinary excretion. Decreased miR-200b expression, an important post-transcriptional regulator of ZEB1 and ZEB2 was also observed. Conclusion Our data demonstrated that VitD deficiency contributes to the rapid development and progression of DKD in diabetic rats induced by increase ZEB1/ZEB2 expressions and miR-200b downregulation.